Controlling the Crystallinity and Morphology of Bismuth Selenide via Electrochemical Exfoliation for Tailored Reverse Saturable Absorption and Optical Limiting - Hao Yan; Bingxue Li; Junjie Pan; Xuan Fang; Yongji Yu; Dengkui Wang; Dan Fang; Yanyan Zhan; Xiaohua Wang; Jinhua Li; Xiaohui Ma; Guangyong Jin (Nanomaterials)
As an emerging two-dimensional (2D) Group-VA material, bismuth selenide (Bi2Se3) exhibits favorable electrical and optical properties. Here, three distinct morphologies of Bi2Se3 were obtained from bulk Bi2Se3 through electrochemical intercalation exfoliation. And the morphologies of these nanostructures can be tuned by adjusting solvent polarity during exfoliation. Then, the nonlinear optical and absorption characteristics of the Bi2Se3 samples with different morphologies were investigated using open-aperture Z-scan technology. The results reveal that the particle structure of Bi2Se3 exhibits stronger reverse saturable absorption (RSA) than the sheet-like structure. This is attributed to the higher degree of oxidation and greater number of localized defect states in the particle structure than in the sheet-like structure. Electrons in these defect states can be excited to higher energy levels, thereby triggering excited-state and two-photon absorption, which strengthen RSA. Finally, with increasing the RSA, the optical limiting threshold of 2D Bi2Se3 can also be increased. This work expands the potential applications of 2D Bi2Se3 materials in the field of broadband nonlinear photonics.